Treadmill exercise modifies dopamine receptor expression in the prefrontal cortex of the 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine-lesioned mouse model of Parkinson's disease. Issue 15 (18th October 2017) - Kintz, Natalie; Petzinger, Giselle M.; Jakowec, Michael W.
Abstract : Parkinson's disease (PD) is the second most common neurodegenerative disorder for which there is no cure. PD is a dopamine (DA)-deficit disorder marked by progressive motor and nonmotor disturbances, including cognitive impairment. Executive function (EF) is the most common subtype of cognitive impairment in PD and consists of deficits in number of processes including behavioral flexibility. The prefrontal cortex (PFC) is an important brain region subserving EF. Furthermore, DA plays a key neuromodulatory role in the PFC and altered DA neurotransmission is believed to contribute toward EF deficits in PD. The mechanisms underlying PFC dysfunction are not fully understood and there are no effective treatments for EF deficits in PD. Exercise is a promising therapeutic strategy that may exert beneficial effects on PFC function in PD. Our previous work suggests that exercise improves motor function and restores striatal DA-D2 receptor (DA-D2 R) expression after DA depletion. This study builds upon our previous work by exploring whether exercise modulates PFC function, specifically DA levels and DA receptor expression in the 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-mouse model of DA depletion. We found that exercise restores PFC DA levels, reverses the MPTP-induced increase in DA-D1 R and decrease in DA-D4 R, and exerts differential effects on D2 Rs. The modest effect of exercise in PFC function may suggest that other types of exercise, such as those that are more skill based, would be required to target these cognitive behavioral circuits.